STRATEGI PENGEMBANGAN PROGRAM STUDI MANAJEMEN DAKWAH FAKULTAS DAKWAH DAN KOMUNIKASI UIN RADEN FATAH DENGAN KERANGKA SWOT - Candra Darmawan; Munqizah Husna Bt Zaidi; Anang Walian (Wardah, 2018)
The purpose of this research is to know and meet the development plan of Manajemen Dakwah Deparment, UIN Raden Fatah in period 2017-2020. This is based on a tracking of the reality of the new study da'wah management process and requires new strategies. The analysis was performed using the SWOT framework. Methodologically this study was conducted using a qualitative approach described descriptively. The results of this study show that there are still many weaknesses in the MD program, in addition to the strength and opportunities available. Therefore, there needs to be a special strategy of socialization and publication, maturing and adjusting the curriculum, multiplying MoU with various other parties, conducting student practice in related institutions, reproducing scientific works and concrete lecturer's work, doing their own procurement to complete laboratory needs, encouraging lecturers to continuing S-3 studies, cooperation with other parties for the procurement of laboratory equipments, working on cooperation that impact on the improvement of infrastructure and infrastructure facilities. Keywords : Development, Management, Dakwah